Establishing biological and environmental drivers that influence the health assessment index as a biomonitoring tool - Phala, Balance Matseilane (My University, 2019)
In South Africa, a high anthropogenic demand of water for domestic, recreational, agricultural, urbanisation and industrial purposes has placed enormous pressure on freshwater resources and has led to a decline in water quality. In addition to measuring water quality variables, the health assessment index (HAI) advocated by AvenantOldewage and Swanepoel (1993), and modified by Crafford and Avenant-Oldewage (2009) by incorporating the inverted parasite index (IPI), and adapted further by Madanire-Moyo et al. (2012) who excluded the white blood cells counts, has been used as a rapid and inexpensive means of assessing and monitoring fish health and, in turn, the state of aquatic ecosystems. However, few studies have evaluated the latter approach in conjunction with other biomonitoring indices to assess the water quality of impoundments. Thus, the aim of this study was twofold. The first was to evaluate the HAI adapted by Madanire-Moyo et al. (2012) as a means to establish the health status of Oreochromis mossambicus (Peters, 1852) sampled from various impoundments based on a once-off survey. The second was to establish if the adapted HAI, in conjunction with selected biomonitoring indices and environmental variables, could describe monthly and seasonal fluctuations of O. mossambicus health. Once-off surveys were conducted between April and May 2016 at five impoundments. The Luphephe-Nwanedi Dam located in the upper catchment of the Limpopo River System and Rhenosterkop Dam situated in the Elands River, a tributary of the Olifants River System, served as control sites due to little or no anthropogenic activities occurring in their catchment areas. In addition, surveys were conducted at Loskop and Flag Boshielo dams and Phalaborwa Barrage situated in the main stem of the Olifants River for comparison purposes. The latter three impoundments were selected because they vary in water quality and pollution levels. Monthly surveys were carried out at Flag Boshielo Dam from February 2016 to February 2017 to establish if the biomonitoring tools and the quantification of water and sediment quality variables, could describe and predict seasonal fluctuations in the health of O. mossambicus. To this end, water quality variables were measured during each survey. Water and sediment samples were collected for analysis of nutrients and metals. Oreochromis mossambicus were collected using gill nets. Fish health was assessed using the adapted HAI that was based on observing parasite burden, haematocrit determination and anomalies in body tissues and organs in conjunction with determining gonad and iv hepato-somatic indices, the condition factor, blood glucose levels, microscopy analyses of fish gills and metal concentrations in fish muscle tissues. Water quality in terms of pH, total dissolved solids and electrical conductivity, nutrients and some aqueous and sediment metals exhibited significant differences (p ˂ 0.05) between impoundments surveyed with water quality from good to poor being in the order of: Luphephe-Nwanedi Dams ˂ Rhenosterkop Dam ˂ Loskop Dam ˂ Phalaborwa Barrage ˂ Flag Boshielo Dam. The HAI scores varied significantly (p ˂ 0.0001) between impoundments and substantiated water quality variables results during once off surveys, indicating that the health of fish from Flag Boshielo Dam were most affected when compared to the health of fish surveyed from the other impoundments. Findings from monthly surveys conducted at Flag Boshielo Dam indicated better conditions in terms of water quality variables during a period of high inflow as opposed to periods of low inflow. The HAI scores obtained for fish exhibited significant (p ˂ 0.0001) differences between the months surveyed and were found to be in agreement with the water quality findings, indicating that flow regimes and water quality of an impoundment have an impact on fish health. The condition and somatic indices findings did not seem to be sensitive enough to discriminate between the impoundments during the once off surveys. While during monthly surveys, these indices were significantly (p ˂ 0.0001) different between the months, showing to be affected by seasonal fluctuations. Knowledge of the HAI in conjunction with blood glucose levels, gill histopathology and the arithmetic mean thickness of gill epithelium (Har) best described the health of fish in both the once off and monthly surveys. In conclusion, the findings of this study emphasised the HAI premise that fish from more polluted sites would be more impacted as opposed to less impacted sites, making the HAI adapted by Madanire-Moyo et al. (2012) an effective and rapid biomonitoring tool that can be used in the field. Furthermore, this study proved that the HAI can be used either solely or in association with the parasite index (PI) or IPI depending on the objectives of the study, as no pronounced differences were evident when using HAI, HAI with PI and HAI with IPI.
Thesis (MSc.) Zoology)) -- University of Limpopo, 2019
Keywords: Water quality; Fresh water; Health assessment index; Water pollution; Water quality -- South Africa; Water quality biological assessment; Water -- Pollution; Fishes -- Histopathology